APPLICATION OF QOWAID FIQHIYYAH IN CONTEMPORARY ISLAMIC LAW - Prawitra Thalib (Yuridika, 2016)
Qawaid fiqhiyyah is a very important element in the contemporary application of Islamic law for the reason that values contained in the fiqiyyah qowaid is a pulse in any fiqh in-the-istinbath of contemporary Islamic jurists. Not only that qowaid fiqiyyah is a parameter benefit whether law is needed or not, but also its main role to ensure that any fiqh in istinbathkan does not contradict the texts, namely the Quran and Sunnah. By applying qowaid fiqiyyah into every attempt of making or interpreting a law, it can be ascertained that law meets the standards to be applied in contemporary society, so it is not feared that the law would lead to new problems or a conflict of norms to apply. Islamic law and qowaid fiqhiyyah have interrelationship with one another, this is because the dynamism of Islamic law embodied in fiqh is very dependent on qowaid fiqhiyyah, in this case the characteristic of the generality or generality of the rules that make the Islamic law can be applied to all Conditions at all times and times.